AUXIN RESPONSE FACTOR3 Regulates Compound Leaf Patterning by Directly Repressing PALMATE-LIKE PENTAFOLIATA1 Expression in Medicago truncatula - Peng, Jianling; Berbel, Ana; Madueño, Francisco; Chen, Rujin (Frontiers in Plant Science, 2017)
Diverse leaf forms can be seen in nature. In Medicago truncatula, PALM1 encoding a Cys(2)His(2) transcription factor is a key regulator of compound leaf patterning. PALM1 negatively regulates expression of SGL1, a key regulator of lateral leaflet initiation. However, how PALM1 itself is regulated is not yet known. To answer this question, we used promoter sequence analysis, yeast one-hybrid tests, quantitative transcription activity assays, ChIP-PCR analysis, and phenotypic analyses of overexpression lines and mutant plants. The results show that M. truncatula AUXIN RESPONSE FACTOR3 (MtARF3) functions as a direct transcriptional repressor of PALM1. MtARF3 physically binds to the PALM1 promoter sequence in yeast cells. MtARF3 selectively interacts with specific auxin response elements (AuxREs) in the PALM1 promoter to repress reporter gene expression in tobacco leaves and binds to specific sequences in the PALM1 promoter in vivo. Upregulation of MtARF3 or removal of both PHANTASTICA (PHAN) and ARGONAUTE7 (AGO7) pathways resulted in compound leaves with five narrow leaflets arranged in a palmate-like configuration. These results support that MtARF3, in addition as an adaxial-abaxial polarity regulator, functions to restrict spatiotemporal expression of PALM1, linking auxin signaling to compound leaf patterning in the legume plant M. truncatula.